2021
DOI: 10.1371/journal.pone.0260160
|View full text |Cite
|
Sign up to set email alerts
|

Employment outcomes and experiences of people with seeing disability in Canada: An analysis of the Canadian Survey on Disability 2017

Abstract: Background Many individuals with disabilities face barriers to meaningful employment. Legislation has been put in place to ensure employment equity for individuals with disabilities in Canada. However, little is known about the employment profile and experiences of people with seeing disabilities. Objectives The objectives of our research study were to explore the employment rates of people with seeing disabilities in Canada, the factors associated with being employed, and supports and barriers that affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
0
9
0
4
Order By: Relevance
“…The 2017 Canadian Survey on Disability estimated that there were 6.2 million individuals with disability in Canada, up from 3.8 million in 2012 4,5 . The number of individuals with disability rose from 13.7% of the Canadian Population in 2012 to 28.1% of the population in 2017, a fact attributed to both increased life expectancy as well as a greater awareness and documentation of disabilities in Canada 4,5 .…”
Section: Background and Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2017 Canadian Survey on Disability estimated that there were 6.2 million individuals with disability in Canada, up from 3.8 million in 2012 4,5 . The number of individuals with disability rose from 13.7% of the Canadian Population in 2012 to 28.1% of the population in 2017, a fact attributed to both increased life expectancy as well as a greater awareness and documentation of disabilities in Canada 4,5 .…”
Section: Background and Aimmentioning
confidence: 99%
“…4,5 The number of individuals with disability rose from 13.7% of the Canadian Population in 2012 to 28.1% of the population in 2017, a fact attributed to both increased life expectancy as well as a greater awareness and documentation of disabilities in Canada. 4,5 These trends are not limited to Canada and have been the basis for the suggestion that graduating dentists in the 21 st century need to be able to provide dental care to individuals with special healthcare needs. 2,6,7 Given that every dental practitioner will encounter individuals with special health care needs in their practice, it has been suggested that rather than a niche specialty, Special Care Dentistry (SCD) should be an integral part of the training of all dentists.…”
Section: Background and Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADA has the potential to affect the lives of substantial numbers of people. One estimate places the number of people with disabilities at 43 million (Gupta, 2021), while another based on category or type of impairment suggests there are approximately 33 million people with sensory, motor, or cognitive disabilities severe enough to interfere with work or otherwise constitute a serious disability (Wong, 2021). These studies also cite 14 million adults (about 7% of the population) who have fourth grade or lower reading skills, which seriously impairs their capability for doing many kinds of jobs, especially those in information occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate of unemployment among PWD is lower in industrialized nations, the estimated figure is between 50 and 70 percent (UN 2007). Several factors including stigma and discrimination, prejudicial attitudes, unfair employment practices, and physical barriers such as spatial and transport challenges have been implicated in the low employment rate of PWD (Araten-Bergman 2016; Gupta, Sukhai, and Wittich 2021; Naami, Hayashi, and Liese 2012; Van Laer, Jammaers, and Hoeven 2022). Low involvement of PWD in the labor market negatively impacts their well-being (Konrad et al 2012) and has adverse economic implications due to reduced productivity (Farrell and Krahn 2014; Vornholt et al 2018).…”
Section: Introductionmentioning
confidence: 99%